Teacher preparation and continuous professional development: A review of ‘missing links’ - Samson John Mgaiwa; Joseph Reginard Milinga (Social Sciences and Humanities Open, 2024)
This paper examines the ‘missing links’ inherent in Tanzania's teacher education to argue for renewed thinking in preparing teachers for the twenty-first century. It does so by employing a narrative literature review as its research approach and reflective perspectives on educational debates regarding the quality of teachers in the country to construct new knowledge. Our findings call for new reforms in recruiting and training teachers to incorporate the assessment and promotion of non-cognitive attributes of potential teachers, contrary to the current practice that emphasises cognitive characteristics at the expense of the former. In addition, initial teacher education and Continuous Professional Development (CPD) are inseparable entities informed by university-school partnerships, hence the need to treat them as such. These findings may interest policymakers, researchers, and state actors on a local, regional, and global scale. For example, our recommendations to employ comprehensive assessment procedures when admitting potential teacher candidates and train them by incorporating and promoting non-cognitive attributes vital for twenty-first-century teachers are relevant across contexts.